1968
DOI: 10.1097/00007890-196808000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Chronic thoracic duct fistula: operative technic and physiologic effects in man

Abstract: LYMPHOCYTE removal through external thoracic duct fistulae causes persistent lymphocytopenia and atrophy of peripheral lymphoid tissue in the experimental animal.y,10 The primary immune response to antigenic stimulation is similarly diminished.14 Clinically, fluid retention in hepatic cirrhosis with ascites and congestive heart failure has been benefited by chronic depletion of lymph.5'7Stimulated by the work of Dumont,6 Bloomstrand,2 and Artz,I we have employed thoracic duct drainage as an adjunct to immunosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…In surgical interventions described in the literature, following unsuccessful conservative treatment most procedures performed were ligation of identified leak or suturing [1,9,15,16,[18][19][20][21][22]. In cases were leakage was present, however, fistula origin could not be identified; hemostyptic devices and fibrin glue were administered with inconsistent success [1,9,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In surgical interventions described in the literature, following unsuccessful conservative treatment most procedures performed were ligation of identified leak or suturing [1,9,15,16,[18][19][20][21][22]. In cases were leakage was present, however, fistula origin could not be identified; hemostyptic devices and fibrin glue were administered with inconsistent success [1,9,16].…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, medium-chain triglycerides (MCT) and short-chain triglycerides are directly absorbed by the portal circulation, the rationale behind conservative management dietary protocols exclusively administering MCT [10][11][12][13]. Subsequent complications of persistent lymph fistula may involve infection, metabolic, and nutritional derangement as well as cosmetic and potentially oncologic disadvantages [2,5,14,15]. Independent of conservative or surgical treatment, the incidence of lymph fistula considerably prolongs hospital stay, expenses, and efforts following thyroid surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of lymphocytes remaining in blood are similar to those present in the lymph during the later stages of collection. The time required for the lymphocyte count in blood to return to normal after drainage is discontinued is variable with the following values reported: 1 month [31], 15 weeks [33], and > 5 months [30].…”
Section: Immunologic Effects Of Chronic Lymphocyte Depletionmentioning
confidence: 99%
“…50% of the donors showed a mild decrease in percentage of B cells, but T cells were unaffected [28], In the second study, after 5-9 leukapheresis procedures, donors were found to have a reduction in the percent of T cells but no alteration of in vitro reactivity in MLC or mitogen response [32], In neither study was the recovery time of the peripheral blood lymphocyte levels mentioned. Lymphocyte depletion and immunosuppression can cer tainly be induced for therapeutic purposes by thoracic duct drainage [33][34][35][36][37][38][39] or lymphocytapheresis of 2.5xlO10 cells per week using protocols specifically designed to re move T lymphocytes. Lymphocyte levels may then remain low for up to a year [40],…”
Section: Discussionmentioning
confidence: 99%